Effects of 3,3’,4,4’,5-pentachlorobiphenyl on in vitro oocyte maturation in dusky tripletooth goby, Tridentiger obscurus: an implication of estrogenic potency - Hwang, In Joon; Baek, Hea Ja (Frontiers in Marine Science, 2023)
Polychlorinated biphenyls (PCBs) are endocrine-disrupting chemicals that mimic estrogen in fish. Among the various PCBs, 3,3’,4,4’,5-pentachlorobiphenyl (PCB126), considered an estrogen antagonist, has been reported to elicit estrogenic activity in fish. We investigated the estrogenic potency of PCB126 in in vitro oocyte maturation in dusky tripletooth goby, Tridentiger obscurus. In this study, we quantified steroid metabolites following exposure to PCB126 and estradiol-17β (E2). Vitellogenic ovarian follicles were incubated, in vitro, with 10 and 100 ng/mL PCB126 or E2 with [3H]17α-hydroxyprogesterone as a precursor. Testosterone (T) and E2, were identified using thin-layer chromatography, high-performance liquid chromatography, and gas chromatography-mass spectrometry. Both PCB126 and E2 increased T and E2 metabolite production. Further, vitellogenic ovarian follicles were exposed to PCB126 (1, 10 and 100 ng/mL) or E2 (0.01, 0.1 and 1 ng/mL) in vitro, and T and E2 from the incubation media were measured. PCB126 (100 ng/mL) inhibited T production and increased E2 production. Furthermore, we investigated the effects of PCB126 on the final oocyte maturation process. Germinal vesicle migration ovarian follicles were in vitro incubated with 0.1, 1, 10 and 100 ng/mL of PCB126 or E2. High doses of PCB126 (10 and 100 ng/mL) inhibited germinal vesicle breakdown. These results suggest that PCB126 has an estrogenic potency in oocyte maturation in T. obscurus.